Possibilities of Desensitisation to Pet Allergens: Prevention of Allergic Reactions in Children and Adults - Lisiecka, Maria Zofia (International Journal of Child Health and Nutrition, 2025)
Purpose: The article aimed to study modern approaches to the desensitization of pet allergens, focusing on advanced therapeutic and diagnostic methods for managing and preventing allergic reactions in children and adults. Material and Methods: The study used a theoretical analysis of scientific sources covering the molecular mechanisms of allergy, modern diagnostic methods, and therapeutic strategies. Results: Global trends in the prevalence of allergies were examined, the role of molecular diagnostics and the latest desensitization methods, such as allergen-specific immunotherapy (ASIT), was assessed, and a comparison of traditional and innovative treatment approaches was made. The findings of the study demonstrate that pet allergy is a globally widespread problem affecting 20-30% of the population of developed countries, with the highest rates among urban populations. It has been established that molecular mechanisms, in particular the role of Fel d 1 and Can f 1, are key to developing an allergic reaction, which opens up opportunities for developing new therapeutic approaches. Modern diagnostic approaches, including molecular component analysis, basophil activation test, and multiplex tests, accurately detect allergens and determine severe reaction risk. Numerous clinical researches have indicated that ASIT utilizing modified allergens reduces allergy symptoms in people with Fel d 1 and Can f 1 sensitization. Conclusion: These results highlight the importance of introducing modern diagnostic methods and personalized therapy in the treatment of animal allergies. This opens up new prospects for improving patients’ lives and reducing the socioeconomic burden of allergic diseases.